Non-participation bias in health services research using data from an integrated electronic prescribing project: the role of informed consent - Bartlett, Gillian; Tamblyn, Robyn M.; Kawasumi, Yuko; Poissant, Lise; Taylor, Laurel (Acta Bioethica, 2005)
Electronic prescribing potentially reduces adverse outcomes and provides critical information for drug safety research but studies may be distorted by non-participation bias. 52,507 patients and 28 physicians were evaluated to determine characteristics associated with consent status in an electronic prescribing project. Physicians with less technology proficiency, seeing more patients, and having patients with higher fragmentation of care were less likely to obtain consent. Older patients with complex health status, higher income, and more visits to the study physician were more likely to consent. These systematic differences could result in significant non-participation bias for research conducted only with consenting patients.